Micro-nano composite activated carbon fiber felt, its preparation method and application
By preparing micro and nano composite activated carbon fiber mats, combining activated carbon fibers with bacterial cellulose nanofibers, the problems of slow adsorption rate at the micron level and poor mechanical properties at the nano level were solved, achieving efficient adsorption and environmentally friendly VOCs treatment.
Patent Information
- Application Number
- CN202410863740.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-29
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-06-29
Smart Images

Figure CN118807716B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of VOCs adsorption composite material technology, specifically relating to a micro / nano composite activated carbon fiber felt, its preparation method, and its application. Background Technology
[0002] Currently, common adsorbent types include molecular sieves, clay, metal-organic framework materials, and porous carbon materials. Among them, porous carbon materials have the characteristics of large specific surface area, controllable pore structure, adjustable pore size, good chemical stability, and easy preparation. Among the many porous carbon materials, activated carbon fiber, as an adsorbent, combines the advantages of conventional porous activated carbon with the characteristics of high aspect ratio and good flexibility of fiber materials. Thanks to the large number of short and straight micropores on the fiber surface and the interconnected pores between fibers, adsorbent materials composed of carbon nanofibers exhibit faster adsorption and desorption efficiency for VOCs compared to traditional activated carbon. In addition, by using different textile processing technologies, activated carbon fibers can be processed into specific shapes (felt, belt, cloth, etc.) according to application requirements, providing more possibilities for the design of VOCs adsorption and separation equipment. However, there are still some problems with the adsorption of VOCs by existing carbon fiber materials: (1) the adsorption rate of micron-sized activated carbon fibers is still not fast enough when adsorbing VOCs, thus affecting the adsorption efficiency; (2) the mechanical properties of nano-sized carbon fiber materials are poor, and they cannot be directly applied to industry, thus affecting future industrialization development.
[0003] The VOCs adsorption device disclosed in domestic patent CN208878213U uses activated carbon as the adsorbent, which solves the problem of VOCs adsorption capacity to a certain extent. However, the specific surface area and adsorption rate of activated carbon particles as adsorbents are still not large enough. Therefore, foreign patent KR1020190050240A uses activated carbon fiber as the adsorbent, which has a high specific surface area and narrow pore size and a high absorption capacity for VOCs. However, compared with carbon nanofibers, the adsorption rate of activated carbon fiber for VOCs is still not fast enough. The technologies disclosed in domestic patents CN107201645A and CN111501206A both use carbon nanofibers as VOCs adsorbents, which solves the problem of improving the adsorption rate to a certain extent. However, carbon nanofibers themselves are brittle and have poor mechanical properties, making them technically difficult to use in industry. Although materials composed of carbon nanofibers and metal frames have certain mechanical properties, they use a lot of chemical raw materials, which also has an impact on environmental issues.
[0004] Micro- and nano-composite activated carbon fiber felt combines activated carbon fiber felt with carbon nanofibers. It is prepared through a series of conditions, including optimization of fiber types, ratios, and concentrations, followed by carbonization treatment. Carbon fibers possess advantages such as abundant microporous structure, high porosity, and high specific surface area, making them promising for VOCs adsorption. However, due to the insufficient adsorption rate of micron-sized carbon fibers and the poor mechanical properties of nano-sized carbon fibers, there is currently no effective technology to achieve the composite of micron- and nano-sized carbon fibers. Therefore, developing an environmentally friendly micro- and nano-composite activated carbon fiber felt is of great significance for further improving VOCs adsorption performance and expanding its application areas. Summary of the Invention
[0005] Technical problems to be solved:
[0006] This application addresses the technical challenges of combining micron and nano materials in existing technologies, as well as the technical problems related to the adsorption of existing micron- and nano-scale composite fibers. It provides a micro / nano composite activated carbon fiber felt, its preparation method, and its application.
[0007] Technical solution:
[0008] To achieve the above objectives, this application provides the following technical solution:
[0009] A method for preparing micro / nano composite activated carbon fiber felt, specifically including the following steps:
[0010] Step 1: Place the activated carbon fiber felt in a forced-air drying oven to remove moisture and dry it thoroughly to a constant weight;
[0011] Step 2: Dilute the bacterial cellulose nanofibers and process them with a high-speed disperser to obtain an aqueous dispersion of bacterial cellulose nanofibers;
[0012] Step 3: Combine the constant-weight activated carbon fiber felt from Step 1 with the uniformly dispersed bacterial cellulose nanofiber aqueous dispersion from Step 2.
[0013] Step 4: Remove the composite activated carbon fiber felt from Step 3 and freeze it after it stops dripping.
[0014] Step 5: Freeze-dry and carbonize the activated carbon fiber felt after the treatment in Step 4 to obtain the micro and nano composite activated carbon fiber felt.
[0015] Furthermore, the first step of the activated carbon fiber felt is a viscose-based activated carbon fiber felt, and the drying temperature is 60°C.
[0016] Furthermore, in the second step, the bacterial cellulose nanofibers are diluted with deionized water to concentrations of 0.1%, 0.2%, and [other concentrations not specified in the original text].
[0017] Aqueous dispersions of bacterial cellulose nanofibers were obtained by treating the 0.3% and 0.4% concentrations in a high-speed disperser at 1000 r / min for 30 min.
[0018] Furthermore, the third composite method is impregnation, with an impregnation ratio of 1:100 (mass ratio of activated carbon fiber felt to bacterial cellulose nanofiber aqueous dispersion).
[0019] Furthermore, in the third step, the composite method is needle injection. Take 10 times the mass of the activated carbon fiber felt and put the bacterial cellulose nanofiber aqueous dispersion into a syringe. Divide the activated carbon fiber felt into a nine-square grid. The injection point is the intersection of each grid line. Insert the needle into the activated carbon fiber felt to inject the liquid.
[0020] Furthermore, in the fourth step, freezing is performed by placing the item in a refrigerator for 16 hours or by rapidly freezing it in liquid nitrogen.
[0021] Furthermore, the freezing process involves placing the item in a refrigerator for 16 hours.
[0022] Furthermore, in the fifth step, the freeze-drying time is 36 hours; the carbonization temperature in the carbonization treatment is 600°C, and the holding time is 2 hours.
[0023] A micro / nano composite activated carbon fiber felt prepared by any of the above preparation methods, wherein nano-sized carbon fibers are wound on micron-sized carbon fibers, and this structure exists both on the outside and inside of the fiber felt.
[0024] This application also discloses the application of micro / nano composite activated carbon fiber felt in VOCs adsorption.
[0025] Explanation of the principle: Existing research shows that carbon nanofibers and activated carbon fibers are two excellent adsorbents for VOCs. By loading short carbon nanofibers onto the surface and interior of activated carbon fiber felt, the two are combined, altering their surface functional groups and enhancing their adsorption properties.
[0026] VOCs provide more adsorption sites, resulting in a faster adsorption rate and a larger adsorption capacity.
[0027] Beneficial effects:
[0028] This application provides a micro / nano composite activated carbon fiber felt, its preparation method, and its application. Compared with the prior art, it has the following advantages:
[0029] 1. This invention patent technology uses micron-sized and nano-sized carbon fibers to adsorb VOCs. Compared with other porous carbon materials, micron-sized activated carbon fibers have the advantages of conventional porous carbon and the characteristics of high aspect ratio and good flexibility of fiber materials. Nano-sized carbon fibers have the characteristics of high specific surface area, small pore size, high porosity and good pore connectivity. Combining the advantages of both can effectively improve the adsorption rate and adsorption capacity of VOCs.
[0030] 2. The patented technology of this invention uses nano-sized carbon fibers and micron-sized carbon fibers to intertwine. Although carbon nanofibers play an important role in improving the adsorption rate and adsorption amount of VOCs, carbon nanofibers have poor mechanical properties. Micron-sized activated carbon fibers have a certain degree of flexibility, which makes up for this shortcoming. The mechanical properties of the composite activated carbon fibers obtained after the two are combined are maintained.
[0031] 3. The patented technology of this invention uses cellulose as raw material, the precursor of activated carbon fiber felt is viscose, and the nanofiber is bacterial cellulose fiber. Compared with other fibers, cellulose fiber has recyclability and biodegradability. Therefore, the micro and nano composite activated carbon fiber felt obtained by combining the two has low pollution in future industrialization.
[0032] 4. BET test results show that the specific surface area of the original activated carbon fiber felt is 1079 m². 2 The specific surface area of both micro and nano composite activated carbon fiber felt increased, especially that of micro and nano composite activated carbon fiber felt with a loading concentration of 0.3% reached 1169 m². 2 The static adsorption test results showed that the original activated carbon fiber felt had an adsorption capacity of only 309 mg / g for n-hexane, while the micro and nano composite activated carbon fiber felt had adsorption capacities of 475, 495, 536, and 510 mg / g for n-hexane (loading concentrations of 0.1%, 0.2%, 0.3%, and 0.4%). The factors that increased the adsorption capacity included not only the increased specific surface area but also changes in surface functional groups. XPS detection revealed that the surface oxygen content of the micro and nano composite activated carbon fiber felt was significantly higher than that of the original activated carbon fiber felt, and the number of oxygen-containing functional groups was also increased. The increase in adsorption capacity is likely the result of the combined effects of physical and chemical adsorption. Attached Figure Description
[0033] Figure 1 These are physical images of the activated carbon fiber mat and bacterial cellulose nanofibers used in this application;
[0034] Figure 2 These are physical images and SEM images of the micro- and nano-composite activated carbon fiber felt of this application, with the left image being the physical image of the micro- and nano-composite activated carbon fiber felt and the right image being the SEM image of the micro- and nano-composite activated carbon fiber felt.
[0035] Figure 3 This is an adsorption curve of n-hexane for the micro / nano composite activated carbon fiber felt and the activated carbon fiber felt of this application. Detailed Implementation
[0036] The following detailed embodiments further illustrate the present invention. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading this disclosure, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.
[0037] The activated carbon fiber felt used in the following examples is a viscose-based activated carbon fiber felt (1 mm thick) provided by Jiangsu Sutong Carbon Fiber Co., Ltd., and the nanofiber is a commercially available bacterial cellulose nanofiber aqueous dispersion (concentration of 0.8%). The activated carbon fiber is dried in a forced-air oven at a drying temperature of 60°C. The composite fiber felt is dried using a freeze dryer, with a total freezing and drying time of 52 hours. The carbonization treatment of the micro and nano composite activated carbon fiber felt is carried out in a vacuum tube furnace at a carbonization temperature of 600°C and a holding time of 2 hours. The adsorption performance test of the micro and nano composite activated carbon fiber felt is conducted using a static adsorption test at a temperature of 25°C and a humidity of 45% ± 5%.
[0038] Example 1:
[0039] A method for preparing micro / nano composite activated carbon fiber felt, specifically including the following steps:
[0040] Step 1: Place the viscose-based active fiber felt in a forced-air drying oven to remove moisture, and dry it thoroughly at 60℃ until constant weight;
[0041] Step 2: Dilute the bacterial cellulose nanofiber aqueous dispersion and disperse it at 1000 r / min for 30 min to prepare four concentrations of 0.1%, 0.2%, 0.3%, and 0.4%.
[0042] Step 3: The viscose-based activated carbon fiber felt that has been weighed and constant is immersed in four different concentrations of bacterial cellulose nanofiber aqueous dispersions at a ratio of 1:100. The mixture is pressed repeatedly five times and then removed until no more liquid drips.
[0043] Step 4: Place the non-dripping viscose-based activated carbon fiber in a refrigerator for 16 hours to freeze;
[0044] Step 5: Place the frozen sample into a freeze dryer for 36 hours of vacuum freeze drying;
[0045] Step 6: The sample after vacuum freeze-drying is subjected to carbonization treatment at a temperature of 600℃ for 2 hours. After cooling in the tube furnace, it is taken out to obtain micro and nano composite activated carbon fiber felt.
[0046] Tests showed that the micro / nano composite activated carbon fiber felt obtained in this embodiment had the highest adsorption capacity for n-hexane up to 541 mg / g. The four samples containing different concentrations of bacterial cellulose carbon nanofibers all maintained their original mechanical properties and showed a slight improvement.
[0047] Example 2:
[0048] A method for preparing micro / nano composite activated carbon fiber felt, specifically including the following steps:
[0049] Step 1: Place the viscose-based active fiber felt in a forced-air drying oven to remove moisture, and dry it thoroughly at 60℃ until constant weight;
[0050] Step 2: Dilute the bacterial cellulose nanofiber aqueous dispersion and disperse it at 1000 r / min for 30 min to prepare four concentrations of 0.1%, 0.2%, 0.3%, and 0.4%.
[0051] Step 3: Aspirate the four concentrations of bacterial cellulose nanofiber aqueous dispersion into a syringe, take 10 times the mass of the activated carbon fiber felt in the syringe, divide the activated carbon fiber felt into a nine-square grid, and inject the liquid into the intersection of each grid line.
[0052] Step 4: Place the viscose-based activated carbon fibers infused with bacterial cellulose nanofibers into a refrigerator and freeze for 16 hours;
[0053] Step 5: Place the frozen sample into a freeze dryer for 36 hours of vacuum freeze drying;
[0054] Step 6: The sample after vacuum freeze-drying is subjected to carbonization treatment at a temperature of 600℃ for 2 hours. After cooling in the tube furnace, it is taken out to obtain micro and nano composite activated carbon fiber felt.
[0055] Tests showed that the micro / nano composite activated carbon fiber felt obtained in this embodiment had a higher adsorption capacity for n-hexane than the original viscose-based activated carbon fiber felt, and all four types of micro / nano composite activated carbon fiber felts containing different concentrations of bacterial cellulose carbon nanofibers maintained their original mechanical properties.
[0056] Comparative Example 1:
[0057] To verify the effect of effective composite of bacterial cellulose carbon nanofibers and viscose-based activated carbon fiber mat on improving VOCs adsorption performance, this comparative example used the same static adsorption test method. The viscose-based activated carbon fibers were dried to constant weight before hexane adsorption. The results showed that the adsorption capacity of viscose-based activated carbon fibers without bacterial cellulose carbon nanofiber composite was 309 mg / g, which was lower than the adsorption capacity of micro / nano composite activated carbon fiber mat for hexane.
[0058] The specific embodiments of the present invention have been described above. It should be understood that the present invention is not limited to the specific embodiments described above, and those skilled in the art can make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A method for preparing micro / nano composite activated carbon fiber felt, characterized in that, Specifically, the steps include the following: Step 1: Place the activated carbon fiber felt in a forced-air drying oven to remove moisture and dry it thoroughly to a constant weight. The activated carbon fiber felt in Step 1 is a viscose-based activated carbon fiber felt. Step 2: Dilute the bacterial cellulose nanofibers and process them with a high-speed disperser to obtain an aqueous dispersion of bacterial cellulose nanofibers. Step 3: Combine the constant-weight activated carbon fiber felt from Step 1 with the uniformly dispersed bacterial cellulose nanofiber aqueous dispersion from Step 2; the composite method in Step 3 is needle injection, take 10 times the mass of activated carbon fiber felt in a syringe, divide the activated carbon fiber felt into a nine-square grid, and inject the liquid into the intersection of each grid line. Step 4: Remove the composite activated carbon fiber felt from Step 3 and freeze it after it stops dripping. The freezing in Step 4 is either placed in a refrigerator for 16 hours or placed in liquid nitrogen for rapid freezing. Step 5: The activated carbon fiber felt processed in Step 4 is freeze-dried and carbonized to obtain the micro and nano composite activated carbon fiber felt; the freeze-drying time in Step 5 is 36 hours; the carbonization temperature in the carbonization treatment is 600℃ and the holding time is 2 hours.
2. The method for preparing micro / nano composite activated carbon fiber felt according to claim 1, characterized in that, The drying temperature in the first step is 60°C.
3. The method for preparing micro / nano composite activated carbon fiber felt according to claim 1, characterized in that, In the second step, the bacterial cellulose nanofibers were diluted with deionized water to concentrations of 0.1%, 0.2%, 0.3%, and 0.4%, respectively. After being treated with a high-speed disperser at 1000 r / min for 30 min, an aqueous dispersion of bacterial cellulose nanofibers was obtained.
4. The method for preparing micro / nano composite activated carbon fiber felt according to claim 1, characterized in that: The freezing process involves placing the item in a refrigerator and freezing it for 16 hours.
5. A micro / nano composite activated carbon fiber felt prepared by any one of the preparation methods described in claims 1-4, characterized in that: Nanoscale carbon fibers are wound around micron-scale carbon fibers, and this structure exists both on the outside and inside of the fiber felt.
6. The application of the micro / nano composite activated carbon fiber felt according to claim 5 in VOCs adsorption.
Citation Information
Patent Citations
Metal organic framework / carbon nanofiber composite membrane material and preparation method thereof
CN107201645A
Carbon nanofiber / CoS2 / MoS2 composite film as well as preparation method and application thereof
CN111501206A
The utility model discloses a VOCs adsorption and desorption activated carbon box
CN208878213U
Method of producing activated carbon fiber
KR1020190050240A
